A SOCIOLOGICAL ANALYSIS OF WOMEN POVERTY RELATED CRIMES WITH SPECIAL REFERENCE TO VIOLENT CRIMES, DRUG TRAFFICKING AND HUMAN TRAFFICKING IN NIGERIA - ESIRI, May O.; OLELE, Hilda E. (International Journal of Psychosocial Rehabilitation, 2020)
Crimes committed by women are increasing in Nigeria especially in the areas of violence, drug and human trafficking as the country's poverty level is growing. It becomes therefore necessary to investigate this phenomenon to contribute to knowledge that will help to bring an end to this growing trend in women's criminality. The study used primary data drawn from a cross-sectional survey of 450 randomly sampled participants from six states of Nigeria which consisted of women between the ages of 18-65 years. Questionnaires were administered to these participants and their responses were analyzed using the descriptive and inferential statistical techniques. Results of the analysis revealed that whereas poverty significantly influences women violent and drug trafficking activities, it has no significant influence on their participation in human trafficking. As a result, this paper concludes that no doubt, poverty is a contributory factor to women increasing criminality in violent crimes and drug trafficking. Hence it is strongly recommended among others that the Nigerian government should actualize free education, free medical treatment, school children feeding scheme and low-cost housing scheme in particular, for women single-parent families in its 36 states.